Assessment of GPS Accuracy in Detecting Simulated Reservoir Subsidence - Zakaria, Zuhaiza (IRC, 2016)

(untitled)
Reservoir subsidence is one of the most common occurrences at the production zone. This is due to the large amount of hydrocarbon that was removed during the production of oil and gas that had caused the depletion and compaction of the reservoir. Hence, the purpose of this study is to verify the capability of the analytical approach by using GPS instrument to detect the probability subsidence that was calculated by the numerical model. Therefore on the basis of the numerical approach, a model that was called Geertsma model was developed to predict the possible subsidence that occurs in the platform. There are two types of GPS that were used in this project which are Static GPS and Real Time Kinematic (RTK) so that they can verify and detect the possible subsidence that was simulated by the model.